Antibiotic resistance of non-fermenting Gram-negative bacilli in a tertiary hospital in Niger: a prospective cross-sectional study - Cyriaque Degbey; Souleymane Brah; Ounoussa Tapha; Abdourahamane Yacouba; Nafissa Mamoudou Issa Koukou; Imrana Abass Albana; Sahada Moussa Saley; Yahayé Hanki; Boutchi Mounkaila; Mahamadou Doutchi; Saidou Mamadou (BMJ Open, 2025)
Objective This study aimed to determine the prevalence and antimicrobial susceptibility profile of non-fermenting Gram-negative bacilli (NFGNB) isolated from clinical samples in a tertiary care hospital in Niger.Design Prospective, cross-sectional study.Setting The study was carried out in a tertiary care hospital in Niger.Participants All clinical samples received at the bacteriology laboratory during the study period for diagnostic purposes were included.Results Out of 548 clinical Gram-negative isolates, 60 strains of NFGNB (10.94%) were isolated. These NFGNB strains were mainly isolated from male patients (62%, n=37) with a mean age of 41.2±27.3 years. NFGNB was more frequent in urine samples (91.7%), followed by pus (6.6%). Among the NFGNB strains isolated, Acinetobacter baumannii was predominant (60%), followed by Pseudomonas aeruginosa (18.3%) and Stenotrophomonas maltophilia (13.33%). 20% (n=12) of NFGNB isolated were multidrug-resistant (MDR), including 13.33% (n=8) carbapenem-resistant A. baumannii and 6.67% (n=4) carbapenem-resistant P. aeruginosa. There is no statistically significant association between MDR-NFGNB and age, sex and origin of patients (p>0.05).Conclusions Our study revealed a relatively high MDR-NFGNB prevalence rate in a Nigerien tertiary care hospital. These findings emphasise the need for vigilant antibiotic stewardship, with appropriate infection prevention and control practices to curb the emergence and spread of MDR-NFGNB infections in hospital settings.